Significant blood protozoan infections, their host range and trend of infections in domestic animals of Malaysia diagnosed by the department of veterinary services and veterinary research institute (VRI) from 1931 to 2010 - a historical preview - Chandrawathani, P.; Tan, T.K.; Adnan, M.; Erwanas, A.I.; Premaalatha, B.; Low, K.N.; Moo, K.S.; Soon, X.Q.; Lim, Y.A.L.; Ramlan, M. (Department of Veterinary Services Malaysia, 2014)
Blood protozoan diseases are significant to animal breeding as they result in economic loss due to mortality, reduction in production efficiency and increment in drugs usage. This historical retrospective study was carried out to investigate the most significant blood protozoan diseases, their trends as well as the host range diagnosed by Veterinary Research Institute (VRI) from 1931 to 2010 among Malaysian domestic animals. Conventional techniques such as stained thin blood film, whole blood buffy coat examination and direct wet smears were utilised for diagnosis from 1931 to 2010. Five most common significant blood protozoan diseases from the domestic animals were identified namely, theileriosis, leucocytozoonosis, plasmodiasis, babesiosis and trypanosomiasis respectively. The setting up of a systematic laboratory service in VRI has enabled more cases of blood protozoan infections to be diagnosed and this has inadvertently led to better understanding and control of the diseases thereby improving the livelihood and reducing economic loss of local farmers.